PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA KELAS IV SDN. No. 054/XI MUARA AIR - Suryani Suryani (Universitas Batanghari Jambi, 2017)
Reading is one part of the language skills to be mastered by an individual. Students can read the passage fluently, but not all students are able to understand the content of the reading material. Therefore, this study aims to improve the ability of primary school students' reading comprehension through the implementation of cooperative learning model Student Teams Achievement Division (STAD). This study is a class action research that involved 10 fourth grade students at SDN. No. 054 / XI Muara Air, Sungai Penuh City, Jambi Province. The study was conducted in January through June 2016. The study was conducted in two cycles and each cycle consisted of four activities: planning, implementation, observation, and reflection. Data were analyzed using descriptive statistics and independent samples t-test. The results showed that the implementation of cooperative learning model STAD can increase the student’s average value from 47 (before action) to 65.5 (the end of the first cycle) and 72 (the end of the second cycle). The average value of the class after the action is higher than the average value of the class before action. In addition increasing of the student’s average value, students in mastery learning outcomes also increased from 40% (before action) to 70% (end of the first cycle) and 80% (second cycle). Thus, teachers can use the cooperative learning model STAD to improve students' skills in reading comprehension.Key words: Indonesian Language, reading comprehension, elementary school students, STAD